Strengthening the Three-Level TNA: The Key to Improving the Competence of Ministry of Religious Affairs Employees - Hikal Husein (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
Optimization of public services at the Ministry of Religious Affairs is significantly hampered because the Education and Training (Diklat) program has not effectively addressed the low employee competency, which is rooted in a weak Training Needs Analysis (TNA). The current TNA process tends to be limited to surveying work unit desires and driven by budget quota pressures, rather than based on an in-depth performance gap analysis between actual competencies and job competency requirements, as mandated by Government Regulation 11/2017. This diagnostic failure is exacerbated by the minimal involvement of direct superiors in curriculum validation, resulting in irrelevant training materials, ultimately hindering knowledge transfer to the workplace. This policy analysis aims to formulate transformative regulatory recommendations to address the root of this problem. The method used is a qualitative policy analysis, including problem identification based on the Three-Level TNA Theory (Noe, 2020) and the Systemic Training Model (Goldstein & Ford, 2002), evaluation of the root causes, formulation of four alternative regulatory policies, and scoring the alternatives using William N. Dunn's criteria (Dunn, 2018). The analysis results indicate that the alternative with the highest score is strengthening TNA standards. Therefore, it is recommended that the Minister of Religious Affairs Regulation (PMA) be established on the Three-Level Mandatory Minimum Standards for TNA and Performance-Based Curriculum Validation to transform training from an administrative activity into a data-driven strategic investment, ensure relevant employee competency, and improve the quality of the Ministry of Religious Affairs' public services.